"German Labour History is Back"—Announcing the Foundation of the German Labour History Association. (2020) - Berger, Stefan
Abstract : When the curtain closed on the first conference of the German Labour History Association (GLHA) that dealt with the topic "Freedom of Labour under Capitalism" and took place at the Institute for Social Movements, Ruhr-Universität Bochum, from February 6 to 8, 2020, the sixty plus members that had been in attendance were agreed: "German Labour History is back." This was a statement that was repeated on the banner of the GLHA proudly presenting its logo and summarizing its ambitions to unite all labor historians across German-speaking areas.